Early Administration of Infliximab for Severe Ipilimumab-Related Diarrhea in a Critically Ill Patient. (June 2014) - Merrill, Steven P.; Reynolds, Paul; Kalra, Avash; Biehl, Jason; Vandivier, R. William; Mueller, Scott W.
Objective: To report a case of ipilimumab-associated life-threatening diarrhea responding quickly to a single dose of infliximab.Case Summary: A 67-year-old man presented 3 weeks after his second dose of ipilimumab with severe diarrhea, acute kidney injury, and hypotension. After 2 days of high-dose corticosteroids and supportive care, he continued to have 2.8 L of stool output per day (grade 4 National Cancer Institute Common Terminology Criteria for Adverse Events). The patient was transferred to the medical intensive care unit requiring endotracheal intubation because of concerns of worsening mental status, metabolic acidosis, and increased work of breathing, with a serum bicarbonate concentration of <5 mmol/L. Despite aggressive fluid resuscitation and a sodium bicarbonate infusion, he remained hypotensive and hyponatremic with persistent premature ventricular contractions. On the evening of day 3, infliximab (5 mg/kg) was given, resulting in a rapid decrease in diarrhea. After 48 hours, the acidosis was corrected and electrolytes, renal function, and fluid status were improving. At discharge, diarrhea, acute kidney injury, and acidosis had resolved, and he was discharged on a slow steroid taper.Discussion: Autoimmune colitis is a described immune-related adverse event of ipilimumab. Prompt recognition, initiation of steroids, and supportive therapy are key to the management of diarrhea. Infliximab should be considered early in steroid-nonresponsive or life-threatening diarrhea.Conclusion: Infliximab is a life-saving intervention in patients with ipilimumab-induced diarrhea.